2010
DOI: 10.48550/arxiv.1003.2196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of Spectator Fragments at an electron Ion collider

Sebastian White,
Mark Strikman

Abstract: Efficient detection of spectator fragments is key to the main topics at an electron-ion collider (eIC). Any process which leads to emission of fragments or γ's breaks coherence in diffractive processes. Therefore this is equivalent to non-detection of rapidity gaps in pp collisions. For example, in coherent photoproduction of vector mesons their 4-momentum transfer distribution would image the "gluon charge" in the nucleus in the same way that Hofstadter measured its charge structure using elastic scattering o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It was suggested that high precision measurement of the transverse momenta of J/ψ would allow one to determine the t dependence of the γ+A → J/ψ+A amplitude and, hence, determine the transverse distribution of gluons in nuclei using a Fourier transform of the amplitude. Unfortunately the processes γ +A → J/ψ+A * , where A * denotes excited nuclear states which decay into the ground state and a photon (photons), dominate the cross section beyond the first minimum making it very difficult to observe the coherent channel beyond the first minimum [236]. At the same time, if the precision measurements of the t dependence at t ∼ 0 are feasible, it would be possible to check the change of the t slope as compared to the impulse approximation, which we find to be of the order of 10 − 15% depending on x, see the discussion of b 2 in Sec.…”
Section: Predictions For the Ratio Of Vector Meson (J/ψ υ) Productionmentioning
confidence: 99%
“…It was suggested that high precision measurement of the transverse momenta of J/ψ would allow one to determine the t dependence of the γ+A → J/ψ+A amplitude and, hence, determine the transverse distribution of gluons in nuclei using a Fourier transform of the amplitude. Unfortunately the processes γ +A → J/ψ+A * , where A * denotes excited nuclear states which decay into the ground state and a photon (photons), dominate the cross section beyond the first minimum making it very difficult to observe the coherent channel beyond the first minimum [236]. At the same time, if the precision measurements of the t dependence at t ∼ 0 are feasible, it would be possible to check the change of the t slope as compared to the impulse approximation, which we find to be of the order of 10 − 15% depending on x, see the discussion of b 2 in Sec.…”
Section: Predictions For the Ratio Of Vector Meson (J/ψ υ) Productionmentioning
confidence: 99%